Gradient bionic wood-based collagen bone-cartilage repair scaffold, preparation method and application

By preparing a gradient bionic wooden-based collagen bone-cartilage repair bracket, the problem of unable to copy the complex structure of the natural bone cartilage tissue of the existing bracket materials, realize the high bionic and gradient mechanical properties of the bracket material, significantly promoted the significant promotion Cell differentiation and osteochromist tissue regeneration.

CN119367602APending Publication Date: 2025-01-28COLLAGEN (WUHAN) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410622173.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing scaffolding materials for bone-cartilage repair cannot replicate the complex structure of natural osteocartilage tissue, especially the directional pore structure of the subchondral bone layer, resulting in its shortcomings in mechanical strength and cell growth promotion.

Method used

By using yak collagen, sodium phosphate, sodium phosphate, calcium chloride, and white wood, use one-step frozen drying technology to prepare a gradient mixture-based collagen bones Composition with the bottom layer, the surface layer is a porous structure connected to each other. The underlying layer is a directed channel structure arranged, and the mechanical properties are enhanced from the surface layer to the bottom layer.

Benefits of technology

This bracket material has excellent biological activity, which can promote the gradient differentiation of osteogenetic stem cells into cartilage cells and osteocytes, significantly enhance the recycling ability of osteochoconia tissue, and show great potential in the treatment of orthopedic arthritis treatment. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367602A_ABST
    Figure CN119367602A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly relates to a gradient bionic wood-based collagen bone-cartilage repair scaffold and a preparation method and application thereof.The scaffold comprises a surface layer, a middle layer and a bottom layer, the surface layer is composed of collagen, the middle layer is composed of collagen and nano-hydroxyapatite, and the bottom layer is composed of collagen and nano-hydroxyapatite; the bottom layer is composed of wood, collagen and nano-hydroxyapatite, the scaffold is obtained by stacking the surface layer, the middle layer and the bottom layer and then conducting freeze-drying, the structure of the scaffold is similar to that of natural osteochondral cartilage, the surface layer is of a porous structure communicated with one another, and the bottom layer is of a directionally-arranged pore channel structure; the main composition of a natural bone cartilage tissue can be highly simulated, and the gradient is presented; the bone marrow mesenchymal stem cell prepared by the method has the advantages of high mechanical performance, gradient enhancement from the surface layer to the bottom layer, excellent biocompatibility and biological activity, capability of remarkably promoting cell proliferation and gradient differentiation of bone marrow mesenchymal stem cells, and application to osteochondral tissue regeneration and clinical treatment of osteoarthritis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a gradient bionic wood-based collagen bone-cartilage repair scaffold, a preparation method and an application thereof. Background Art

[0002] Osteoarthritis is a widespread degenerative joint disease. Severe osteoarthritis often leads to the formation of osteochondral defects. Tissue transplantation is a common method for treating osteochondral defects in clinical practice, but it has significant drawbacks, such as limited tissue sources, immune rejection, and the risk of disease transmission. Although autologous chondrocyte transplantation has also been developed for the treatment of osteochondral defects, its wide clinical application is severely limited due to the limited cell sources and high surgical costs.

[0003] Biomimetic scaffold materials have attracted much attention in osteochondral tissue engineering because they can simulate the structure and function of natural tissues. A series of multiphase biological scaffolds have been developed for the treatment of osteochondral defects by simulating the hyaline cartilage layer, calcified cartilage layer and subchondral bone layer of natural osteochondral tissue. Although these scaffold materials effectively replicate the complex composition of natural osteochondral tissue, they cannot replicate the complex structure of natural osteochondral tissue, especially the subchondral bone layer.

[0004] In natural osteochondral tissue, subchondral bone is composed of subchondral bone plate and subchondral sponge, which is separated from the calcified area of ​​articular cartilage by bone cement line. It is mainly composed of collagen and in situ mineralized hydroxyapatite. Subchondral bone has excellent mechanical strength. The anatomical structure of this area shows a directional channel structure perpendicular to the articular surface. [1]-[2] . This special directional pore structure not only makes the subchondral bone have a good supporting effect, but also can effectively transmit nutrients and promote cell proliferation and migration. However, the existing scaffolds for bone-cartilage repair are only bionic in composition and cannot produce scaffolds with directional pore structures. Therefore, the development of scaffold materials with highly bionic natural bone cartilage complex structures is still an urgent problem that needs to be solved.

[0005] The inventor unexpectedly prepared a gradient biomimetic wood-based collagen bone-cartilage repair scaffold by using yak collagen, sodium dihydrogen phosphate, calcium chloride and delignified white wood using a one-step freeze-drying technique. Not only is the main composition highly similar to natural osteochondral tissue, it also presents a clear gradient. The structure of the scaffold is highly biomimetic of natural osteocartilage, with its surface layer presenting an interconnected porous structure and the bottom layer being a directional pore structure. The mechanical strength of the scaffold material increases gradually from the surface layer to the bottom layer. The scaffold has excellent biological activity, can promote the gradient differentiation of bone marrow mesenchymal stem cells into chondrocytes and osteoblasts, and has great potential in the regeneration of osteochondral tissue and the treatment of osteoarthritis.

[0006] References:

[0007] [1]Madry,H.,van Dijk,CN,Mueller-Gerbl,M.The basic science of the subchondral bone[J].Knee Surg.Sport Tr.A.2010,18(4):419-433.

[0008] [2]Wei, W., Dai, H. Articular cartilage and osteochondral tissue engineering techniques: Recent advances and challenges[J]. Bioact.Mater.2021,6(12):4830-4855. Summary of the invention

[0009] In view of the above technical problems, the purpose of the present invention is to provide a gradient bionic wood-based collagen bone-cartilage repair scaffold, the scaffold includes three layers: a surface layer, a middle layer and a bottom layer: the surface layer is composed of collagen, the middle layer is composed of collagen and nano-hydroxyapatite, the bottom layer is composed of wood, collagen and nano-hydroxyapatite, and the scaffold is obtained by gradient freeze-drying after stacking the surface layer, the middle layer and the bottom layer.

[0010] Preferably, the wood is delignified wood.

[0011] Preferably, the nano-hydroxyapatite is formed by in-situ mineralization of sodium dihydrogen phosphate and calcium chloride using collagen as a biological template.

[0012] The second object of the present invention is to provide a method for preparing the gradient bionic wood-based collagen bone-cartilage repair scaffold, the method comprising the following steps: (1) dissolving collagen in an acetic acid solution to form a uniform solution, adjusting the pH to 7.4, adding a PBS solution, incubating at 37° C., centrifuging, cross-linking the obtained precipitate with a cross-linking agent, centrifuging, washing, and obtaining a surface gel;

[0013] (2) Collagen is dissolved in acetic acid solution to prepare a collagen solution, the pH value is adjusted to 7.4, a calcium chloride solution is added, and after being stirred evenly, a sodium dihydrogen phosphate solution is added, and the pH value is adjusted to 7.4, the mixture is stirred for reaction, and centrifuged. The obtained precipitate is cross-linked with a cross-linking agent, centrifuged, and washed to obtain a middle layer gel;

[0014] (3) Wood soaked in NaClO 2The solution was deligninized, washed with ethanol, and freeze-dried; the solution was immersed in a collagen solution, vacuumed, and freeze-dried; the solution was alternately mineralized in a 500 mM calcium chloride solution and a 300 mM sodium dihydrogen phosphate solution at 37°C for 6 days, and the solution was fully washed to obtain a bottom matrix;

[0015] (4) The surface gel prepared in step (1), the middle gel prepared in step (2), and the bottom matrix prepared in step (3) are stacked in sequence, pre-frozen at -35°C for 10 hours, and subjected to gradient freeze-drying, the procedure being: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1 hour; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; and maintained at 25°C for 16 hrs to obtain a scaffold.

[0016] Preferably, the collagen is one or more of animal type I collagen, type II collagen, and type III collagen.

[0017] Preferably, the collagen is yak type I collagen.

[0018] Preferably, the crosslinking agent in steps (1) and (2) is 0.1 wt% BDDE, and crosslinking is performed at room temperature.

[0019] The third object of the present invention is to provide the use of the stent or the stent prepared by the preparation method in the preparation of biomaterials and / or medical devices.

[0020] The fourth object of the present invention is to provide the use of the scaffold or the scaffold prepared by the preparation method in the preparation of products promoting bone and cartilage tissue regeneration.

[0021] The fifth objective of the present invention is to provide the use of the stent or the stent prepared by the preparation method in the preparation of drugs for preventing or treating osteoarthritis.

[0022] The beneficial effects of the present invention are as follows: (1) The present invention provides a gradient bionic wood-based collagen bone-cartilage repair scaffold, the scaffold comprising a surface layer, a middle layer and a bottom layer: the surface layer is composed of collagen, the middle layer is composed of collagen and nano-hydroxyapatite, the bottom layer is composed of wood, collagen and nano-hydroxyapatite, and the scaffold is obtained by gradient freeze-drying after stacking the surface layer, the middle layer and the bottom layer; (2) The structure of the scaffold is similar to that of natural osteocartilage, the surface layer is an interconnected porous structure, and the bottom layer presents a directional arranged pore structure; it can highly biomimetic the main components of natural osteocartilage tissue and present a gradient; (3) The mechanical properties of the scaffold are gradiently enhanced from the surface layer to the bottom layer; (4) The scaffold has excellent biocompatibility and bioactivity, can significantly promote cell proliferation and gradient differentiation of bone marrow mesenchymal stem cells, and can be applied to osteocartilage tissue regeneration and clinical osteoarthritis treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Characterization of the physicochemical properties of scaffold materials Note: SZ: surface layer; MZ: middle layer; BZ: bottom layer; TWMC: three-layer wood-based mineralized collagen; Among them: A is the surface photograph of TWMC scaffold material; B is the SEM image of TWMC scaffold material; C is the SEM image of SZ scaffold material; D is the SEM image of MZ scaffold material; E is the SEM image of BZ scaffold material; F is the TEM image of SZ; G is the TEM image of MZ; H is the TEM image of BZ; I is the XRD image of SZ, MZ and BZ scaffold materials; J is the FT-IR image of SZ, MZ and BZ scaffold materials; K is the TGA image of SZ, MZ and BZ scaffold materials.

[0024] Figure 2 Mechanical properties of scaffold materials Note: A is the stress-strain curve of SZ scaffold material; B is the stress-strain curve of MZ scaffold material; C is the stress-strain curve of BZ scaffold material; D is the stress-strain curve of TWMC scaffold material; E is the compressive strength of SZ, MZ, BZ and TWMC scaffold materials; F is the compression modulus of SZ, MZ, BZ and TWMC scaffold materials.

[0025] Figure 3 In vitro biocompatibility of scaffold materials Note: A is cytotoxicity; B is cell proliferation; C is live / dead cell staining; D is immunofluorescence staining.

[0026] Figure 4 Osteogenic differentiation on scaffold materials Note: AC is the relative expression of Acan, Col2a1 and Sox9 cartilage genes on scaffold materials; DF is the relative expression of ALP, Col1a1 and Runx 2 osteogenic genes on scaffold materials. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that the reagents used in the following examples, unless otherwise specified, can be purchased from the market.

[0029] In the following examples, it should be noted that SZ is the abbreviation for the surface layer; MZ is the abbreviation for the middle layer; BZ is the abbreviation for the bottom layer; TWMC is the abbreviation for the three-layer wood-based mineralized collagen. In some examples and drawings of the specification, the abbreviations are directly used instead of the full names, which have the same meaning.

[0030] In the following embodiments, the wood used is white wood, but it is not limited to white wood. Any wood with a directional pore structure can achieve the functions described in the present invention and can be used to prepare a bone-cartilage repair scaffold.

[0031] Example 1 Preparation of surface layer (SZ) scaffold

[0032] Yak type I collagen was dissolved in acetic acid solution to form a uniform solution of 3 mg / mL, and its pH was adjusted to 7.4. Then, 2 volumes of PBS solution were added and incubated at 37°C for 4 hours. The precipitate obtained by centrifugation was cross-linked with 0.1wt% BDDE at room temperature for 72 hours. After centrifugal washing, it was pre-frozen at -35°C for 10 hours and then gradient freeze-dried according to the procedure: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1h; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; 25°C for 16hrs to obtain the surface (SZ) scaffold.

[0033] Example 2 Preparation of middle zone (MZ) scaffold

[0034] Yak type I collagen was dissolved in acetic acid solution to prepare a 1 mg / mL collagen solution, and its pH was adjusted to 7.4. Then, 500 mM calcium chloride solution was added and stirred evenly, and then 300 mM sodium dihydrogen phosphate solution was added to adjust its pH to 7.4. After stirring and reacting at 37°C for 24 hours, the precipitate obtained by centrifugation was cross-linked with 0.1 wt% BDDE at room temperature for 72 hours. After centrifugal washing, it was pre-frozen at -35°C for 10 hours, and then gradient freeze-dried according to the procedure: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1h; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; 25°C maintained for 16 hrs to obtain the middle layer (MZ) scaffold.

[0035] Example 3 Preparation of bottom layer (BZ) support

[0036] Wood soaked in NaClO 2 The solution was de-lignined, washed with ethanol, and freeze-dried; it was immersed in a 1 mg / mL collagen solution, vacuumed, and freeze-dried; it was alternately mineralized in a 500 mM calcium chloride solution and a 300 mM sodium dihydrogen phosphate solution at 37°C for 6 days, washed thoroughly, and pre-frozen at -35°C for 10 hours, and then the following procedures were followed: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1h; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; and maintained at 25°C for 16hrs for gradient freeze-drying to obtain the bottom layer (BZ) scaffold.

[0037] Example 4 Preparation of three-layer wood-based mineralized collagen (TWMC) scaffold

[0038] Yak type I collagen was dissolved in acetic acid solution to form a 3 mg / mL uniform solution, the pH of which was adjusted to 7.4, and then 2 volumes of PBS solution were added. After incubation at 37°C for 4 hours, the precipitate obtained by centrifugation was cross-linked with 0.1 wt% BDDE at room temperature for 72 hours, centrifuged and washed to obtain a surface gel;

[0039] Yak type I collagen was dissolved in acetic acid solution to prepare 1 mg / mL collagen solution, the pH of which was adjusted to 7.4, and then 500 mM calcium chloride solution was added. After stirring evenly, 300 mM sodium dihydrogen phosphate solution was added to adjust the pH to 7.4. After stirring and reacting at 37°C for 24 hours, the precipitate obtained by centrifugation was cross-linked with 0.1 wt% BDDE at room temperature for 72 hours, and after centrifugation and washing, a middle-layer gel was obtained;

[0040] Wood soaked in NaClO 2The solution was deligninized, washed with ethanol, and freeze-dried; it was immersed in a 1 mg / mL collagen solution, vacuumed, and freeze-dried; it was alternately mineralized in a 500 mM calcium chloride solution and a 300 mM sodium dihydrogen phosphate solution at 37°C for 6 days, and fully washed to obtain a bottom matrix;

[0041] The surface gel, middle gel and bottom matrix were stacked in sequence, pre-frozen at -35°C for 10 hours, and then subjected to gradient freeze-drying, with the following program: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1h; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; and maintained at 25°C for 16hrs, to obtain a three-layer wood-based mineralized collagen (TWMC) scaffold.

[0042] The morphology of the prepared TWMC scaffold is as follows: Figure 1 As shown in A. The results showed that the TWMC scaffold was in a gradient white sponge shape and had a stable interface bonding.

[0043] Example 5 Physicochemical Characterization of Three-layer Wood-based Mineralized Collagen (TWMC) Scaffold

[0044] (1) The TWMC bracket prepared in Example 4 was fixed on the sample stage. After gold spraying for 25 seconds, the sample morphology was detected using a scanning electron microscope (SEM) at a voltage of 5.0 kV.

[0045] The results of scanning electron microscopy are as follows Figure 1 BE, where 1B is the SEM image of the TWMC scaffold material; 1C is the SEM image of the SZ scaffold material; 1D is the SEM image of the MZ scaffold material; 1E is the SEM image of the BZ scaffold material. The results show that each layer of the TWMC scaffold has a clear boundary and a stable interface; the SZ and MZ structures of the TWCH scaffold present a highly interconnected porous structure; the BZ of the TWMC scaffold presents a directional pore structure, and a large amount of minerals formed are evenly distributed along the directional pores. The results show that the structure of the TWMC scaffold is similar to that of natural osteochondral tissue.

[0046] (2) The SZ, MZ and BZ prepared in (1), (2) and (3) of Example 4 were dispersed in aqueous solution respectively, then dropped onto a copper grid and air-dried, and their nanostructures were characterized using a transmission electron microscope (TEM) at a voltage of 200 kV.

[0047] The results of transmission electron microscopy are as follows Figure 1FH are TEM images of SZ, MZ and BZ, respectively. The results show that only smaller-sized collagen fibers are formed in SZ; MZ has a small amount of in situ mineralized hydroxyapatite crystals distributed along the collagen fibers; BZ shows a large amount of hydroxyapatite crystals distributed along the wood scaffold. The results show that the content of in situ mineralized hydroxyapatite in the TWMC scaffold gradually increases from SZ to BZ.

[0048] (3) The SZ, MZ and BZ scaffolds prepared in Examples 1-3 were placed on a powder X-ray diffractometer (XRD) and their crystal structure types were determined at a scanning rate of 0.02° / s.

[0049] The results are as follows Figure 1 As shown in Figure I, the BZ scaffold showed obvious characteristic peaks at 26.1°, 31.7°, 39.8°, 46.6° and 49.6°, corresponding to the (002), (211), (310), (222) and (213) diffraction planes of hydroxyapatite, respectively; the MZ scaffold showed relatively weak characteristic peaks at 26.1°, 31.7°, 39.8°, 46.6° and 49.6°; while the SZ scaffold did not show the characteristic peaks of hydroxyapatite. The results show that the hydroxyapatite content in the TWMC scaffold gradually increases from SZ to BZ.

[0050] (4) The SZ, MZ and BZ scaffolds prepared in Examples 1-3 were mixed and ground with potassium bromide particles at a mass ratio of 1:100, and then the powders were pressed into transparent sheets for Fourier transform infrared (FT-IR) measurement.

[0051] The results are as follows Figure 1 J shows that the SZ bracket is at 1656cm -1 The C=O peak with collagen characteristics; MZ scaffold at 1036cm -1 、604cm -1 and 558cm -1 The characteristic peaks that appeared were attributed to the phosphate groups in hydroxyapatite; the characteristic peaks of the phosphate groups in the BZ scaffold were significantly enhanced. The results showed that the composition of the TWMC scaffold mainly included collagen and hydroxyapatite, and showed a gradient distribution.

[0052] (5) The SZ, MZ and BZ scaffolds prepared in Examples 1-3 were placed in a crucible of a thermogravimetric analyzer (TGA) and the mass change between 50°C and 800°C was measured at a scanning rate of 5°C / min.

[0053] The results are as follows Figure 1As shown in Figure 1, the remaining mineral content of the BZ scaffold is about 60.2%, the mineral content of the MZ scaffold is about 29.8%, and the SZ scaffold has almost no remaining minerals. The results show that the content and distribution of inorganic matter in the TWMC scaffold are similar to those of natural osteochondral tissue, and show a clear gradient.

[0054] Example 6 Mechanical properties of three-layer wood-based mineralized collagen (TWMC) scaffolds

[0055] According to the steps of Examples 1-4, SZ, MZ, BZ and TWMC scaffolds with a diameter of 15 mm and a thickness of 12 mm were prepared in a mold, and finally a compression test was carried out at a speed of 1 mm / min.

[0056] The results are as follows Figure 2 As shown, 2A is the stress-strain curve of the SZ scaffold material; 2B is the stress-strain curve of the MZ scaffold material; 2C is the stress-strain curve of the BZ scaffold material; 2D is the stress-strain curve of the TWMC scaffold material; 2E is the compressive strength of the scaffold material; and 2F is the compression modulus of the scaffold material.

[0057] The results showed that the compressive strengths of SZ, MZ and BZ scaffolds were 0.053MPa, 0.48MPa and 2.82MPa, respectively, and their compression moduli were 0.08MPa, 0.74MPa and 4.38MPa, respectively; the compressive strength and compression modulus of TWMC scaffolds were 0.93MPa and 1.49MPa, respectively. The results showed that TWMC scaffolds have excellent mechanical strength, and their mechanical properties gradually increase from SZ to BZ.

[0058] Example 7 Biocompatibility of three-layer wood-based mineralized collagen (TWMC) scaffolds

[0059] (1) 100 μL of a solution with a density of 1×10 6 BMSCs suspension with a concentration of 10 cells / mL was added to a 96-well plate and cultured in a cell culture incubator for 24 hours. Subsequently, SZ, MZ, and BZ scaffolds were added to the wells and incubated at 37°C for 24 hours. The Blank group did not receive any treatment. After removing the culture medium, 100 μL of 10% cell counting kit (CCK-8) was added and cultured at 37°C for another 30 minutes. The absorbance value at 450 nm was measured using an ELISA reader.

[0060] The results are as follows Figure 3 As shown in A, after SZ, MZ and BZ scaffolds were co-cultured with cells, the number of living cells exceeded 100%. The results showed that TWMC scaffolds had no cytotoxicity.

[0061] (2) BMSCs were cultured at 1×10 5The cells were seeded at different densities on SZ, MZ, and BZ scaffolds in 24-well plates; meanwhile, BMSCs in the blank group were added to untreated 24-well plates. After incubation in the incubator for 7 and 14 days, 300 μL of 10% CCK-8 solution was added to each well and cultured at 37°C for 30 minutes. 100 μL of supernatant was transferred to a 96-well plate, and the absorbance at 450 nm was measured using an ELISA reader.

[0062] The results are as follows Figure 3 As shown in B, with the increase of culture time, the number of living cells in SZ, MZ and BZ scaffold materials gradually increased and was significantly higher than that in the blank group. The results showed that TWMC effectively promoted cell proliferation.

[0063] (3) The density is 1×10 6 BMSCs suspensions with a concentration of 10 cells / mL were seeded onto the surface of SZ, MZ and BZ scaffolds, respectively, and cultured in α-MEM complete medium for 3 and 7 days, respectively. Calcein-AM and propidium iodide (PI) were used to stain live and dead cells at 37°C for 1 hour. Finally, cell fluorescence images were obtained using a laser confocal microscope.

[0064] The results are as follows Figure 3 C shows the live / dead cell staining of BMSCs cultured on SZ, MZ and BZ scaffold materials for 3 and 7 days, respectively. The results showed that the number of live cells in SZ, MZ and BZ scaffold materials increased with the increase of culture time, and the cells grew along the porous and directional structure of the scaffold. The results showed that the TWMC scaffold has excellent biocompatibility and can significantly promote cell proliferation.

[0065] (4) 1 mL of density is 1×10 5 BMSCs suspensions of 100 cells / mL were inoculated on SZ, MZ and BZ scaffolds. After 7 days of co-culture, the cells were fixed with 4% paraformaldehyde for 15 minutes at room temperature, permeabilized with 0.1% Triton X-100 for 5 minutes, and blocked with 1% BSA for 30 minutes. At 37°C, the cells were stained with phalloidin-tetramethylrhodamine isothiocyanate for 1 hour and Hoechst33258 for 5 minutes. Fluorescence images were collected using a laser confocal microscope.

[0066] The results are as follows Figure 3 D shows the immunofluorescence staining of BMSCs cultured on SZ, MZ and BZ scaffold materials for 7 days. The results show that the cells of SZ, MZ and BZ scaffold materials grow along the porous and directional structure of the scaffold and present a beautiful cytoskeleton. The results show that the TWMC scaffold provides support for cell growth and has good cell adhesion.

[0067] Example 8 Cell differentiation of three-layer wood-based mineralized collagen (TWMC) scaffolds

[0068] (1) The density is 1×10 6 BMSCs suspensions with a concentration of 10 cells / mL were implanted into SZ, MZ, and BZ scaffold materials, respectively, and cultured in α-MEM complete medium for 14 days. The blank group used the same number of cells and culture time, but without scaffold materials. RNA isolation kit was used to extract total RNA, PrimeScript RT reagent Kit and gDNAEraser were used to synthesize cDNA, TB Green Premix Ex Taq II was used to analyze gene expression levels, and Real-Time PCR System was used to detect the expression of cartilage-specific genes. Finally, 2 -ΔΔCT The relative expression of the target gene was calculated by the method, with β-actin as the internal reference gene, and normalized according to the gene expression of the blank group on the 14th day.

[0069] The results are as follows Figure 4 AC shows the relative expression of cartilage differentiation genes Acan, Col2a1 and Sox9 in SZ, MZ and BZ scaffolds. The results showed that after 14 days of co-culture of cells with scaffolds, Acan, Col2a1 and Sox9 genes had the highest gene expression in SZ scaffolds, and the cartilage gene expression in BZ scaffolds was the lowest. The results showed that TWMC scaffolds significantly promoted the gradient cartilage differentiation of bone marrow mesenchymal stem cells.

[0070] (2) The density is 1×10 6 The suspension of 10 cells / mL was planted into SZ, MZ and BZ scaffold materials respectively, and cultured with α-MEM complete medium for 14 days. The blank group used the same number of cells and culture time, but without scaffold materials. The total RNA was extracted using RNA isolation kit, PrimeScript RT reagent Kit and gDNAEraser were used to synthesize cDNA, TB Green Premix Ex Taq II was used to analyze gene expression levels, and Real-Time PCR System was used to detect the expression of osteogenic specific genes. Finally, 2 -ΔΔCT The relative expression of the target gene was calculated by the method, with β-actin as the internal reference gene, and normalized according to the gene expression of the blank group on the 14th day.

[0071] The results are as follows Figure 4DF shows the relative expression of ALP, Col1a1 and Runx 2 genes in SZ, MZ and BZ scaffolds. The results showed that after 14 days of co-culture of cells with scaffolds, ALP, Col1a1 and Runx 2 genes had the highest gene expression in BZ scaffolds, and the osteogenic gene expression in SZ scaffolds was the lowest. The results showed that TWMC scaffolds significantly promoted the gradient osteogenic differentiation of bone marrow mesenchymal stem cells.

[0072] In summary, the present invention provides a gradient bionic wood-based mineralized collagen scaffold, the scaffold comprises a surface layer, a middle layer and a bottom layer: the surface layer is obtained by cross-linking collagen through a cross-linking agent, the middle layer is obtained by cross-linking collagen and nano-hydroxyapatite through a cross-linking agent, and the bottom layer is obtained by cross-linking wood, collagen and nano-hydroxyapatite through a cross-linking agent. The scaffold is obtained by gradient freeze-drying after stacking the surface layer, the middle layer and the bottom layer. The scaffold structure is similar to natural osteocartilage, the surface layer is an interconnected porous structure, and the bottom layer presents a directional arranged pore structure; the main components of natural osteocartilage tissue can be highly biomimetic and present a gradient; the mechanical properties are gradiently enhanced from the surface layer to the bottom layer, it has excellent biocompatibility and biological activity, can significantly promote cell proliferation and gradient differentiation of bone marrow mesenchymal stem cells, and can be applied to osteocartilage tissue regeneration and clinical osteoarthritis treatment.

Claims

1. A gradient bionic wood-based collagen bone-cartilage repair scaffold, characterized in that: The scaffold comprises a surface layer, a middle layer and a bottom layer: the surface layer is composed of collagen, the middle layer is composed of collagen and nano-hydroxyapatite, the bottom layer is composed of wood, collagen and nano-hydroxyapatite, and the scaffold is obtained by stacking the surface layer, the middle layer and the bottom layer and freeze-drying them.

2. The bracket according to claim 1, characterized in that The nano-hydroxyapatite uses collagen as a biological template and is formed by in-situ mineralization of sodium dihydrogen phosphate and calcium chloride.

3. The bracket according to claim 1, characterized in that: The wood is delignified wood.

4. The method for preparing the gradient bionic wood-based collagen bone-cartilage repair scaffold according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) dissolving collagen in an acetic acid solution to form a uniform solution, adjusting the pH to 7.4, adding a PBS solution, incubating at 37° C., centrifuging, cross-linking the obtained precipitate with a cross-linking agent, centrifuging, washing, and obtaining a surface gel; (2) Collagen is dissolved in acetic acid solution to prepare a collagen solution, the pH value is adjusted to 7.4, a calcium chloride solution is added, and after being stirred evenly, a sodium dihydrogen phosphate solution is added, and the pH value is adjusted to 7.4, the mixture is stirred for reaction, and centrifuged. The obtained precipitate is cross-linked with a cross-linking agent, centrifuged, and washed to obtain a middle layer gel; (3) The wood was immersed in a NaClO2 solution for delignification, washed with ethanol, and freeze-dried; immersed in a collagen solution, vacuumed, and freeze-dried; mineralized alternately in a 500 mM calcium chloride solution and a 300 mM sodium dihydrogen phosphate solution at 37°C for 6 days, and washed thoroughly to obtain a bottom matrix; (4) The surface gel prepared in step (1), the middle gel prepared in step (2), and the bottom matrix prepared in step (3) are stacked in sequence, pre-frozen at -35°C for 10 hours, and subjected to gradient freeze-drying, the procedure being: -35°C to -20°C, 5°C / h; -20°C to -15°C, 0.78°C / h, and maintained at -15°C for 1 hour; -15°C to -5°C, 2°C / h; -5°C to 25°C, 7.5°C / h; and maintained at 25°C for 16 hrs to obtain a scaffold.

5. The preparation method according to claim 4, characterized in that: The collagen is one or more of animal type I collagen, type II collagen and type III collagen.

6. The preparation method according to claim 5, characterized in that: The collagen is yak type I collagen.

7. The preparation method according to claim 4, characterized in that: The cross-linking agent in steps (1) and (2) is 0.1 wt% BDDE, and cross-linking is performed at room temperature.

8. Use of the stent according to any one of claims 1 to 3 or the stent prepared by the preparation method according to any one of claims 4 to 7 in the preparation of biomaterials and / or medical devices.

9. Use of the scaffold according to any one of claims 1 to 3 or the scaffold prepared by the preparation method according to any one of claims 4 to 7 in preparing a product for promoting osteochondral tissue regeneration.

10. Use of the stent according to any one of claims 1 to 3 or the stent prepared by the preparation method according to any one of claims 4 to 7 in preparing a drug for preventing or treating osteoarthritis.

Citation Information

Cited By

  • Bionic silk fibroin cartilage scaffold for skull defect repair

    CN121313955A

  • Mineralized collagen cartilage repair scaffold as well as preparation method and application thereof

    CN121338116A